Vitamin E (? tocopherol) attenuates toxicity and oxidative stress induced by aflatoxin in rats - Yilmaz, Seval; Kaya, Emre; Comakli, Selim (Wroclaw Medical Univ, 2017)
Background. Aflatoxins are toxic metabolites produced by Aspergillus flavus and Aspergillus parasiticus and are classified as group I carcinogens by the International Agency for Research on Cancer (IARC). Objectives. The purpose of this study was to investigate the possible preventive role of vitamin E (Vit E) on aflatoxin (AF) induced toxicity by using biochemical and histopathological approaches. Material and methods. Wistar-Albino rats were divided into 4 groups as follows: control group, Vit E group (Vit E was administered), AFB(1) group (a single dose of AFB1 was administered), AF + Vit E group (AF and Vit E were administered). The effects of Vit E on AFB1 induced tissue toxicity were evaluated by using malondialdehyde (MDA), reduced glutathione (GSH) levels, antioxidant enzyme activities, and histopathological examination in tissues. Results. AF caused the oxidative stress by the increased MDA level and the reduced GSH level, glutathione- S-transferase (GST), catalase (CAT), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and glucose-6-phosphate dehydrogenase (G6PD) activities in tissues. Plasma aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) activities, creatinine, and urea concentrations significantly increased; whereas, chloride, phosphorus, and magnesium concentrations were insignificantly affected. Plasma glucose, protein and sodium concentrations significantly decreased. Administration of AF caused hepatotoxicity, cardiotoxicity, and nephrotoxicity. As far as histopathological changes are concerned, a statistically significant difference was found in AFB(1) group compared to the control group. Vit E considerably reduced plasma AST, ALT, ALP, LDH activities, and urea concentration and ameliorated the deleterious effects of AF on oxidative stress markers and pathological changes. Conclusions. This data indicated that the natural antioxidant Vit E might have a protective effect against AF-induced toxicity and oxidative stress.
Keywords: oxidative stress; antioxidant; aflatoxin; vitamin E